DESAIN STRATEGI PEMASARAN ONLINE PADA FULLUS FASHION MELALUI EVALUASI BENCHMARKING - Novia Ayu Putri (Universitas Ciputra Surabaya, 2016)
The purpose of this research is to design the marketing strategy for Fullus Fashion based on their online sales through a benchmarking evaluation. This research is a descriptive qualitative research. Interview and documentation are used as data collection methods. The six informants interviewed in this study include the owners of benchmark companies that have been running for at least five years, shareholders of Fullus Fashion, and an expert in online business strategy. Triangulation is used to test the validity and reliability of the research data, while e- Marketing Mix is used as an analysis tool. The analysis is used to compare the marketing strategies of Fullus Fashion and the benchmark companies. The result of this study is a new marketing strategy formula for Fullus Fashion's online sales by means of a benchmark evaluation. In terms of product strategy, the company should add more variants, such as dress, tank top, and crop top. Promotion can be improved by creating a website that will enable the company to send newsletters to consumers containing the latest information and e-coupons. Additionally, online advertising, giveaways, and endorsements can also be implemented to promote the company. In terms of place, the company should try to sell through online marketplaces, such as Zalora or Berrybenka, in order to introduce the brand to the marketplace's traffic.